Dakwah Vigilantisme FPI Memberantas Patologi Sosial: Mencari Solusi Moderat Perspektif Hadits Riwayat Muslim No. 70 - Muhamad Fajri (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Front Pembela Islam (FPI) has gained notoriety for its vigilante-style amar ma'ruf nahy munkar (enjoining what is right and forbidding what is wrong) activities, often bypassing legal authorities. This study scrutinizes the juxtaposition of FPI's physical interventions in da'wah with the three dimensions of da'wah, as outlined in Muslim hadith number 70: yadun (physical), lisan (verbal), and qolby (heart). The research objectives include evaluating FPI's vigilantism in da'wah within a legal framework, reinterpreting it through the lens of Muslim hadith number 70, and proposing a moderate Indonesian context-compliant resolution. Utilizing qualitative methods with a phenomenological approach, this study classifies FPI's actions as vigilantism for social control, straddling Indonesia's legal boundaries. It identifies FPI's physical interventions as a form of yadun da'wah per the aforementioned hadith. To foster moderation, FPI should consider constitutional avenues or opt for lisan and qolby da'wah to prevent vigilante actions. Applying yadun da'wah, as per Muslim hadith number 70, is incongruous with Indonesia's principles, contradicting established positive law and endangering its multicultural and pluralistic values. Lisan and qolby da'wah offer a more moderate and harmonious approach to addressing social pathology.